Nasal cancer and occupational exposures. Preliminary report of a joint Nordic case-referent study. - Hernberg, Sven; Collan, Y.; Degerth, R.; Englund, Anders; Engzell, U.; Kuosma, Eeva; Mutanen, Pertti; Nordlinder, H.; Hansen, H. S.; Schultz-Larsen, K. (Scandinavian Journal of Work, Environment & Health, 1983)
Nasal and sinus paranasal cancers have been associated with several occupational exposures, for example, dust from hardwood, nickel and unspecific agents occurring in the boot and shoe industry. A joint Danish-Finnish-Swedish case-referent investigation was initiated in 1977 to study further the connection between nasal and sinus paranasal cancers and various occupational exposures. All new cases of these cancers were collected from the national cancer registers (Finland & Sweden) or from hospitals (Denmark). Those still alive who agreed to the interview (N = 167) were individually matched for age and sex with patients with colonic or rectal cancer. A detailed telephone interview was performed according to a standardized procedure. Both the cases and referents thought that their condition was the one under study. The exposures were coded blindly by an experienced industrial hygienist. The results showed associations between nasal or sinus paranasal cancer and exposure to hardwood or mixed wood dust (discordant pairs 14/2); softwood dust alone (13/4); chromium 16/6); nickel (12/5, not significant); welding, flamecutting, and soldering (17/16); and lacquers and paints (12/0). Hardwood dust exposure showed a connection with adenocarcinoma. Softwood dust exposure alone was associated with epidermoid and anaplastic carcinomas. No associations were found for a number of exposures, including agricultural chemicals, textile dust, asbestos, quartz dust, organic solvents, and leather work. Possible exposure to formaldehyde was evenly distributed between the cases and referents.